INDONESIAN EFL STUDENTS’ PERCEPTION OF SELF-SELECTED AND TEACHER ASSIGNED WRITING TOPICS - Sitorus, Witya Chairinda (Academy of Education Journal, 2023)
One of the skills that is strengthened in language learning, especially English and foreign languages, is the ability to write. Writing means expressing in writing ideas, opinions, thoughts, and feelings. Familiarity with the topic in writing can be one of the factors that influence students' perceptions of their writing. Topics chosen by students and topics chosen by the teacher provide opportunities for students to convey their perceptions. And this can be developed when writing descriptive text. The purpose of this research is to examine how Indonesian EFL students perceive the writing topics they choose themselves and the topics the teacher chooses through their students' writing by asking them to write descriptive texts as a form of writing. The characteristics in this study are in the form of texts written by participants for researchers, and the resulting data is in the form of an analysis of the participant's writing process. The research method used is a qualitative descriptive research method where data collection is carried out through interview techniques, observation, and document studies. The researcher conducted unstructured interviews by asking questions related to the important points of the problem the participants wanted to explore. The researcher made direct observations of the participants who were working on the assignments given to them. Then the researcher applied the study of primary and secondary documents. The participants in this study were 36 students from 10th grade at one of the public high schools in Tanjungbalai. The results of this study indicate that students are more motivated to write when they are given the right to choose their own topics in writing class as opposed to topics chosen by their teachers.